Body Shaming dalam Perspektif Tafsir Al-Mishbah dan Implikasinya pada Realitas Kekinian - Aulia, Aulia; Taufiq, Muhammad (Darul Yasin Al Sys, 2023)
Allah mentions in one of His words, namely QS. Al-Isra/17: 70 that humans are given advantages over all the creatures that Allah created on this earth, among which humans generally have good physique, the ability to think, freedom of will and knowledge, but not many people have If you want to think about His Word, nowadays it is very easy to find a number of people saying inappropriate words towards each other, especially regarding someone's physical appearance or appearance. This term is known as body shaming, which is an act of physical shaming, an appearance that makes the person feel insecure about their physical appearance. The problem discussed in this research is regarding body shaming verses and the effectiveness of these interpretations in contemporary reality. Meanwhile, this type of research is included in the type of library research, namely by reading and reviewing a number of literature related to the research problem, then processing it and drawing out the common threads. The interpretation method in this research is the mawdhu'iy method which was popularized by Al-Farmawi. The conclusion from the results of this research is a general description of body shaming which consists of the definition, causes and impacts. Then it was added with an introduction to Tafsir Al-Mishbah which was accompanied by its interpretation of several verses, including the QS. al-Hujurat/49: 11, QS. at-Taubah/9: 79, QS. al-Humazah/104:1 and QS. al-Hijr/15:11, from a number of interpretations these are then implicated in contemporary reality. A number of meanings were found in Quraish Shihab's interpretation, including the loss of human feeling in protecting one's word, the loss of a sense of equality, and the loss of human values.